Lack of Association between C385A Functional Polymorphism of the Fatty Acid Amide Hydrolase Gene and Polycystic Ovary Syndrome - Grolmusz, V. K.; Stenczer, B.; Fekete, T.; Szendei, G.; Patócs, A.; Rácz, K.; Reismann, P. (Experimental and Clinical Endocrinology & Diabetes, 2013)
The endocannabinoid system contributes to the regulation of appetite, food intake and energy balance. Fatty acid amide hydrolase is responsible for degradating anandamide, a key messenger of the endocannabinoid system. C385A is a common, functionally active genetic polymorphism of the gene encoding fatty acid amide hydrolase and has been associated with overweight and obesity. Our aim was to establish whether single nucleotide polymorphism C385A has an association with polycystic ovary syndrome or its clinical features.A monocentric pilot study was performed on 63 patients with polycystic ovary syndrome and 67 healthy control subjects. Anthropometric parameters and laboratory data were acquired from subjects. The alleles of the polymorphism were detected using polymerase chain reaction and subsequent cleavage by Eco130I (StyI) restriction endonuclease verified by direct DNA sequencing.No difference was found in minor allele frequency between patient and control groups. Those patients, carrying the C385A polymorphism were associated with higher free thyroxine hormone levels. In the control group, carriers of the polymorphism had significantly lower insulin levels.Our data indicate that the C385A polymorphism of the fatty acid amide hydrolase gene is not a genetic susceptibility factor for the development of polycystic ovary syndrome. However, the polymorphism might have a role in influencing the synthesis or metabolism of different hormones including thyroxin and insulin.
Keywords: FAAH; PCOS; endocannabinoid system; SNP